Respostas
respondido por:
2
A) 18x - 43=65
18x = 65 + 43
18x = 108
x =
x = 6
B) 23x - 16 = 14 - 17x
23x + 17x = 14 + 16
40x = 30
x =
x = 0,75
C) 5x - 8 = 3x - 12
5x - 3x = -12 + 8
2x = - 4
x =
x = - 2
D) x + 4 = 10
x = 10 - 4
x = 6
Espero ter ajudado! ^^
18x = 65 + 43
18x = 108
x =
x = 6
B) 23x - 16 = 14 - 17x
23x + 17x = 14 + 16
40x = 30
x =
x = 0,75
C) 5x - 8 = 3x - 12
5x - 3x = -12 + 8
2x = - 4
x =
x = - 2
D) x + 4 = 10
x = 10 - 4
x = 6
Espero ter ajudado! ^^
jakeipu1:
Ajudou bastante , muito obrigada! *--*
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás